PENDAMPINGAN DIGITALISASI DAN PENGURUSAN NOMOR INDUK BERUSAHA (NIB) UNTUK MENINGKATKAN LEGALITAS UMKM DI DESA CIKALONG - Hardian , Kiki; Rizkyani Putri , Devita; Nurina, Nabila; Sutira , Andri; Nurnaningsih, Rita; Fauziah, Diah; Nur Ramdhan, Rahmat (Jurnal Istimā, 2025)
Business legality is one of the important aspects in developing a business. The Business Identification Number (NIB) is one form of business legality provided by the government. With an NIB, a business owner will obtain legal recognition and easy access to expand their marketing reach. However, mani MSMEs entrepreneurs still face obstacles in obtaining it. Low understanding of the importance of business legality and digital literacy, concerns about data misuse, and digital literacy, concerns about data misuse, and technical obstacles in the OSS system make many entrepreneurs reluctant to register. This study aims to identify the effectiveness of digitalization assistance and NIB creation in increasing the awareness and ability of entrepreneurs in managing their business legality. The method used is Mixed Methods with a Participatory Action Research Approach, which actively involves the community in every stage of its implementation. The result of this study show that the assistance program has successfully helped around 25 MSMEs players in Cikalong Village. This assistance has enabled these business actors to now have business legality (NIB) and understand its benefits. Additionally, this assistance also successfully improves the digital promotion skills of MSMEs entrepreneurs in Cikalong Village, thereby opening opportunities for the sustainability and development of MSMEs in the current economic era.